Radiation dose comparison in brain CT examinations among 3 public hospitals. (September 2016) - Kordolaimi, Sofia; Ploussi, Agapi; Syrgiamiotis, Vassileios; Makri, Triantafillia; Hatzigiorgi, Christiana; Evlogias, Nikolaos; Stratigopoulou, Athanasia; Efstathopoulos, Efstathios
Abstract : Introduction: The higher risk from radiation and the longer life expectancy of children render the estimation of the radiation dose a vital need especially for common radiation-induced procedures like Brain CT. However, effective doses from pediatric Brain CT procedures are scarce in literature. Purpose: The aim of this presentation is to estimate effective doses for pediatric Brain CT examinations performed in 2 public pediatric hospitals and 1 public general hospital. Materials and methods: For that purpose, 160 patients from pediatric hospital 1 (PH1), 130 patients from pediatric hospital 2 (PH2), and 16 patients from general hospital (GH) underwent Brain CT examinations by utilizing age-adjusted scanning protocols was retrospectively reviewed. Acquisition and dosimetric data were extracted from the DICOM header. Age- specific DLP to effective dose conversion coefficients, according to ICRP 103, were applied to console-displayed DLP data. Results: The effective doses for the age categories of 0–1 y, 1–5 y, 5–10 y and 10–15 y were 3.6 ± 1.3 mSv, 3.9 ± 1.6 mSv, 2.9 ± 1.4 mSv, and 2.8 ± 1.1 mSv for PH1, no data for 0–1 y, 2.4 ± 1.4 mSv, 2.3 ± 0.9 mSv, and 2.2 ± 0.8 mSv for PH2 and 3.6 ± 1.3 mSv, 2.5 ± 1.3 mSv, 1.3 ± 0.8, and 1.7 ± 1.0 mSv for PH, respectively. Conclusion: Although CT protocols varied in terms of acquisition parameters and scanning mode, this variety is not depicted in the effective doses which are comparable among the various hospitals for the same age group. Either way, thorough optimization of CT scanning protocols is vital in each and every hospital that treats pediatric patients.